Comparative evaluation of salivary zinc concentration in autistic and healthy children in mixed dentition age group-pilot study - Rahul R Deshpande; Pranav Prakash Dungarwal; Komal K Bagde; Priyadarshini S Thakur; Pankti M Gajjar; Ananth P Kamath (Wolters Kluwer Medknow Publications, 2019)
Context: Autism prevalence is increasing, with current estimates at 1/68-1/50 individuals diagnosed with autism. Diagnosis is based on behavioral assessments. Early diagnosis and intervention are known to greatly improve functional outcomes in people with autism. Diagnosis, treatment monitoring, and prognosis of autistic children's symptoms could be facilitated with biomarkers to complement behavioral assessments. Aims: The aim of this study is to compare and evaluate salivary zinc concentration in saliva samples of autistic and healthy children in mixed dentition age group. Settings and Design: Cross-sectional comparative study carried out in dental college and special child school. Unstimulated whole saliva collected for finding a biomarker. Subjects and Methods: Unstimulated whole saliva sample was collected from 10 autistic and 10 healthy children in mixed dentition age group. Diluted saliva sample was then subjected to inductively coupled plasma emission spectroscopy for the estimation of salivary zinc concentration. Statistical Analysis Used: Mann-Whitney U-test. Results: In children with autism salivary zinc concentration showed a linear equation when compared to healthy children. Conclusions: The low salivary zinc concentration in autistic children can reveal the pathogenesis of autism.